Manajemen Pembiayaan Pendidikan Bersumber dari Masyarakat - Sonedi, Sonedi; Jamalie, Zulfa; Majeri, Majeri (LP2M IAIN Samarinda, 2017)
This study aims to describe the budget plan of income and expenditure of schools, the allocation of educational financing, the supervision of education financing, and the reporting of education financing originating from parents in MTs Darul Ulum Palangkaraya. This research uses qualitative descriptive research method, conducted in MTs Darul Ulum Palangka Raya. Data collection techniques through observation, interview and documentation. The results of this study reveal that the Madrasah Budget PlanÂ in MTs Darul Ulum Palangkaraya has been made through prior planning by the madrasah before meeting with foundations, school committees and parents, although the draft budget is made in the form of The simplest. In the case of the use of parents' funds, the learners are in accordance with the needs and RAPBM made, in the sense that the accounting has been made accounting. Furthermore, supervision of financial management is done directly by the principal.